Posted by bindiya farswani on .
I've to solve 3x^2 + 6x +3 =0 by factoring. Thus, after solving I got the answer as 3(x + 1)^2.
Please correct me if I'm wrong.

math 
Reiny,
3x^2 + 6x +3 =0
first divide each term by 3, the fact that the right side is zero and zero divided by anything is zero, we can just drop the 3
x^2 + 2x + 1 = 0
(x+1)^2 =
take √ of both sides
x+1 = 0
x = 1
You had it factored correctly, but you "lost " your equation by dropping the =0 part. 
math 
bindiya farswani,
Oh, thanks a lot!